Socıal Capıtal To Implement The Socıal Functıonalıty Of Transmıgrant Communıtıes Based On Land Tenure Patterns In Marga Saktı Vıllage, North Bengkulu - Yunilisiah Yunilisiah; Tamrin Bangsu; Desy Afrita (Cita Konsultindo Research Center, 2024)
This research focuses on social capital to provide support in the implementation of social functionality of transmigrant communities based on land tenure patterns in Kuro Sleep village, North Bengkulu Regency. They have occupied this goal for 40 years and have undergone changes in the structure of land tenure. Participatory data collection through direct observation and in-depth interviews and documentation. The data were analyzed with an interactive model based on qualitative interpretation inductively with an emic approach. The results of the study found that transmigration communities have differences in social capital in implementing functionality based on land tenure. Households with narrow land and landless tend to bonding social capital types in an effort to carry out social functionality in the form of strengthening kinship systems and maintaining self-help activities and for social capital types in the form of bridging more emphasis on forms of social action. While the type of social capital linking in the form of strengthening is in the order of self-help groups. Large land households type of social capital bonding in the form of social care and bridging capital elements are strengthening in participation in building social integration in the unity of transmigrant communities. While the type of linking social capital in this strata is in the form of social groups controlled by village elites.